Oxford handbook of adult nursing - Flynn, Maria; Mercer, David, 1957- ([Oxford] : Oxford University Press, 2018)
The second edition of the'Oxford Handbook of Adult Nursing' addresses the philosophy, principles, and practice of general adult nursing, and the ways in which general adult nurses relate to people, engage critically with professional knowledge, and organize appropriate nursing care and interventions.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 5, 2018).
Keywords: Nursing -- Handbooks, manuals, etc